Statement... - Carrington, Edwin W. ([CCS] [Georgetown]GY, 1995)
Highlights recent events in the international system such as the situation in Haiti; the establishment of the Association of Caribbean States; the Summit of the Americas; the launching of the World Trade Organisation; enlargement of the European to incorporate Austria, Finland and Sweden; and, the decision to incorporate Suriname into CARICOM. Looks at developments within CARICOM that are both administrative and internal.